Asrah Batin Tradition: Cultural Values of the Ngombak Village Community and Their Relevance as a Social Sciences Learning Resource for Middle/MTs - Anisa Ussolihah; Dany Miftah M Nur (STKIP Taman Siswa Bima, 2024)
The Asrah Batin tradition is a form of local culture that has cultural values developed in the continuity of tradition by the people of Ngombak Village, Kedungjati District, Grobogan Regency, so that it can benefit life and has potential in the world of education, namely in learning. The aim of this research is to determine the cultural values in the Asrah Batin tradition and their relevance as a social studies learning resource. This type of research is a qualitative study. With a qualitative descriptive approach. The data sources in this research are primary sources and secondary sources. Data collection techniques through observation, interviews and documentation. The data validity technique uses source triangulation. Meanwhile, data analysis uses data reduction techniques, data presentation and conclusions. The research results show that the Asrah Batin tradition in Ngombak Village has cultural values that are developed and preserved by the community. These cultural values include: kinship, social, religious, mutual cooperation, unity, cooperation and mutual respect. These cultural values are related to social studies learning, in the main material